PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS POWERPOINT TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS IV DI SDN 4 PANGGANG KECAMATAN JEPARA KABUPATEN JEPARA - Fitra Khasanatus Sholihah; Ika Ratnaningrum (Postgraduate, University of Mataram, 2025)
This study aims to examine the relationship between the use of interactive PowerPoint media and students’ learning motivation and outcomes in the IPAS (Natural and Social Sciences) subject. Using a quantitative approach with an ex post facto design, the research was conducted on fourth-grade students at SD Negeri 4 Panggang. Data were collected through questionnaires to measure motivation, documentation of test scores to assess learning outcomes, and interviews to provide contextual insights. The results show that students’ learning motivation reached an index value of 86.3%, categorized as high based on predetermined interpretation criteria. The average student learning outcome was 83.60, which falls into the “very good” performance category according to the school’s grading standard. While the study does not establish a causal relationship, the findings indicate a significant contribution of interactive PowerPoint media to students’ motivation and academic achievement. However, the absence of a comparison group and baseline measurements limits the ability to isolate the impact of the media from other influencing factors. Further research with controlled experimental designs is recommended to explore the causal effects of technology-based instructional media in elementary education.